A study on the feasibility of setting up Terminal Makanan Negara (TEMAN) at Kuching Sarawak / Roslan Ahmad Darus - Ahmad Darus, Roslan (2003)
A food wholesale market is a place where producers, manufacturers, importers and traders (wholesalers) subdivide food into small lots and sell large quantities of food goods to shops, canteens, kiosks and other commercial buyers. It is not intended to supply goods directly to housewives 1 . In other words, a wholesale market is allocation where a number of traders (wholesalers) can regularly trade together in order to sell a range of goods that are similar in type to buyers who require goods of different quality, quantity and price.